2021
DOI: 10.3389/fbioe.2021.648366
|View full text |Cite
|
Sign up to set email alerts
|

Fmoc-PEG Coated Single-Wall Carbon Nanotube Carriers by Non-covalent Functionalization: An Experimental and Molecular Dynamics Study

Abstract: Due to their structural characteristics at the nanoscale level, single-walled carbon nanotubes (SWNTs), hold great promise for applications in biomedicine such as drug delivery systems. Herein, a novel single-walled carbon nanotube (SWNT)-based drug delivery system was developed by conjugation of various Fmoc-amino acid bearing polyethylene glycol (PEG) chains (Mw = 2,000, 5,000, and 12,000). In the first step, full-atom molecular dynamics simulations (MD) were performed to identify the most suitable Fmoc-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Aromatic-group molecules can be easily noncovalently bound to CNTs via strong π−π interactions. 19,20 1D functionalized CNTs (f-CNTs) could enhance the binding to a molecule by interacting through several binding sites due to their flexibility. 21 Magnetic carbon nanotubes (mCNTs) have been developed to impart magnetic properties to CNTs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aromatic-group molecules can be easily noncovalently bound to CNTs via strong π−π interactions. 19,20 1D functionalized CNTs (f-CNTs) could enhance the binding to a molecule by interacting through several binding sites due to their flexibility. 21 Magnetic carbon nanotubes (mCNTs) have been developed to impart magnetic properties to CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their large surface area, unique structure, and excellent physical properties, they are among the best nanomaterials for highly effective drug and biomolecule delivery. They can be conjugated noncovalently or covalently with drugs, biomolecules, and nanoparticles. Also, due to their extremely wide surface area, a variety of molecules can multiconjugate on their sidewalls. Aromatic-group molecules can be easily noncovalently bound to CNTs via strong π–π interactions. , 1D functionalized CNTs (f-CNTs) could enhance the binding to a molecule by interacting through several binding sites due to their flexibility …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SWCNTs are highly hydrophobic and must be individually suspended in water to reveal their characteristic fluorescence in the NIR spectral region . Several classes of dispersants are reported to suspend SWCNTs in water, e.g., surfactants, , single-stranded DNA, , amphiphilic polymers, and also proteins, peptoids, and peptides. Several studies showed that (Fmoc-)­conjugated amino acids and peptides are able to disperse SWCNTs in an aqueous environment, , and molecular dynamics simulation showed the hybridization of amino acid crystals with carbon nanotubes. , Further, SWCNTs have proven high biocompatibility in several in vivo applications, rendering them favorable for usage in implantable hydrogels. …”
mentioning
confidence: 99%